DEVELOPMENT OF COGNITIVE ABILITIES IN ENGLISH LESSONS - Tontayeva Aigerim Nurlanovna; Kulakhmetova Mergul Sabitovna (Progress in Science, 2023)
The article discusses the development of cognitive abilities in teaching English: how through the teacher's task system for the formation of universal learning activities in English lessons, the possibility of developing the thinking and abilities of students is provided. A foreign language as a general educational subject can and should contribute to the development of students' creative abilities. Having a huge upbringing, educational and developing potential of students' creative abilities, a foreign language can realize it only in the course of implementing the practical goal of learning, that is, only if the student in the process of foreign language communicative and cognitive activity (listening, speaking, reading, using writing ) will expand their general educational horizons, develop their thinking, memory, feelings and emotions; if in the process of foreign language communication the social and value qualities of the individual will be formed: worldview, moral values and beliefs, character traits.